NEUROIMAGING ELECTROENCEPHAHLOGRAPHY (EEG) APPLICATION ON HUMAN ELECTRICAL BRAIN ACTIVITIES DURING MEDITATION AND MUSIC LISTENING - Helman, A.A.; Amin, M.K.M.; Muzahidul Islam, A.K.M.; Mikami, O. (Journal of Advanced Manufacturing Technology (JAMT), 2019)
Meditation has a positive impact on the life of human beings. Researchers have scientifically measured and reported the positive impact of meditation from various neuroscience and neuroimaging technology such as encephalogram, fMRI, ECG, etc. Therefore, the neurophysiological EEG was used to identify the brain activities after listening to Zikr and compared it to music listening. Five healthy students as subjects were instructed to listen to the Zikr meditation from Asma Ul-Husna and slow rock music. A low-cost 16 electrodes of Emotiv Epoc was used to record the brain waves activities and determined its location in the brain lobes. Statistical analysis by using FFT from the MATLAB EEGLAB Toolbox software was performed to obtain and analyzed the data. The analysis result showed that the right frontal F8 give out high alpha and beta value thus proving that it involves focus and attention. 85% of the lobes involved give out low beta band during listening to Zikr meditation which indicates the person to focus more during Zikr listening session. Hence, Zikr meditation can lead a person into a calmer state when compared to music listening.